FLRA and Its Influence on EFL Students’ Reading Achievement Amid the Pandemic Covid-19 - Anwar Nurul; Mohd Sani Ismail; Ari Safar Wadi (International Journal of English and Applied Linguistics (IJEAL), 2022)
Foreign Language Reading Anxiety (FLRA) is a symptom of anxiety in reading which becomes increasingly challenging for EFL learners. FLRA is an influential interruption that might prevent EFL learners to derive a reading grasp. The pandemic situation borders teachers’ and students’ activities in the learning process. In this condition, numbers of students in Indonesian schools perform different reading comprehension achievements, including low, middle, and high levels. The researcher noted that several Indonesian students feel anxious in the second language (L2) reading with certain reading troubles. The purpose of this study was to examine FLRA and its influence on the students’ reading achievement amid the pandemic COVID-19 schooling including identifying potential factors which affect their anxieties in reading and investigating their influence on their reading achievement. This study used a quantitative research method. The research was carried out in the Eagle Class students of LinkAge education, in Lombok, Indonesia. The sample of this study was 20 students selected using the purposive sampling method. The data were collected using a questionnaire namely the Foreign Language Reading Anxiety Scale (FLRAS) which was developed by Saito et al (1999) with a five-point Likert scale. The researcher analyzed the data using descriptive statistics. The results demonstrate that the students’ anxiety level is 58.25 which indicates that they experience a high level of anxiety although the value is a little bit lower than the limit of moderate level. There are some symptoms of reading anxieties commonly recognized by the students.